Preliminary Prototyping and Simulations to Explore Mechanical Properties of 3D Printed Materials for Supporting the Human Head (Global Journals of Research in Engineering, 2023)
A novel exoskeleton design has been produced that assists the contraction of neck muscles 3D printing has been employed to reduce costs of manufacturer The two printing materials employed were Polylatic acid PLA and polyethylene terephthalate with carbon PET-C and the central spinal cord of the design being Nitrile rubber
Keywords: 3D printing; exo-skeleton; PLA; PETC